2022
DOI: 10.3390/bs12070224
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self-Selected Exercise Workloads on Perceived Enjoyment and Self-Efficacy in Sedentary Adults

Abstract: Self-selected workloads are shown to be more enjoyable than researcher-selected workloads. In addition, it is unclear if sedentary adults find aerobic interval or continuous exercise more pleasant. Therefore, the primary purpose of this study was to determine the effects of two acute bouts (interval vs. continuous) of self-selected moderate-intensity treadmill exercises on perceived enjoyment and self-efficacy towards exercise in a sedentary cohort. Methods: Sixteen sedentary adults completed two 30 min bouts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
0
0
Order By: Relevance
“…There were no significant differences in exercise intensity markers such as HR and RPE between the two sessions. This finding aligns with previous studies that reported similar results for self-selected and imposed exercise intensities in other populations 9,10. Furthermore, the majority of patients maintained an HR >50% of their estimated maximal HR during both sessions, consistent with a prior study11 of PAD patients with claudication symptoms who exercised at the pain threshold and demonstrated HR ranging from 60-82% of maximal HR during the exercise session.…”
Section: Discussionsupporting
confidence: 91%
“…There were no significant differences in exercise intensity markers such as HR and RPE between the two sessions. This finding aligns with previous studies that reported similar results for self-selected and imposed exercise intensities in other populations 9,10. Furthermore, the majority of patients maintained an HR >50% of their estimated maximal HR during both sessions, consistent with a prior study11 of PAD patients with claudication symptoms who exercised at the pain threshold and demonstrated HR ranging from 60-82% of maximal HR during the exercise session.…”
Section: Discussionsupporting
confidence: 91%
“…There is evidence that shows that engaging in PA that is enjoyable, improves health and well-being, and provides continual novel stimulus, will improve engagement and adherence over time. [51][52][53] In this sense, our findings have clearly showed that PA is essential to manage LTCs and maintaining the mental health in an enjoyable way. Therefore, once again our findings demonstrated that 'one-size-fits-all' is not working and more individualised PA guidelines according to the person and each LTC are needed.…”
Section: Pa Is Associated With Better Mental Healthsupporting
confidence: 53%
“…Especially beneficial is participation in group activities, such as square dancing, Tai chi, football, basketball, volleyball, and other activities [45]. Central to these activities is the communication process between people [46], making people feel free and relaxed and able to quickly form positive emotions [47,48].…”
Section: The Mediating Effectsmentioning
confidence: 99%